2002
DOI: 10.1097/01.lab.0000042240.52093.0f
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Defects and Selective Disruption of Basement Membranes in Mice Lacking Entactin-1/Nidogen-1

Abstract: SUMMARY:Entactin-1 (nidogen-1) is an ubiquitous component of basement membranes. From in vitro experiments, entactin-1 was assigned a role in maintaining the structural integrity of the basement membrane because of its binding affinity to other components, such as type IV collagen and laminin. Entactin-1 also interacts with integrin receptors on the cell surface to mediate cell adhesion, spreading, and motility. Targeted disruption of the entactin-1 gene in the mouse presented in this study revealed a duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 49 publications
1
109
0
1
Order By: Relevance
“…However, results from mice where this binding domain was deleted by gene targeting showed that nidogen-laminin binding, although important for the formation of certain basement membranes, is not a general prerequisite for basement membrane assembly (11). Genetic deletion of either of the nidogen genes in the mouse results in only mild changes with no alteration in tissue or basement membrane architecture (12)(13)(14). Further, the finding of a redistribution and up-regulation of nidogen-2 in nidogen-1-deficient animals suggested a partial redundancy within the family (13).…”
mentioning
confidence: 79%
“…However, results from mice where this binding domain was deleted by gene targeting showed that nidogen-laminin binding, although important for the formation of certain basement membranes, is not a general prerequisite for basement membrane assembly (11). Genetic deletion of either of the nidogen genes in the mouse results in only mild changes with no alteration in tissue or basement membrane architecture (12)(13)(14). Further, the finding of a redistribution and up-regulation of nidogen-2 in nidogen-1-deficient animals suggested a partial redundancy within the family (13).…”
mentioning
confidence: 79%
“…Because of the unavailability of entactin/nidogen, we could not investigate its role in MDCK cystogenesis in methylcellulose gels. We predict that nidogen alone would not be sufficient for MDCK cystogenesis, because the ablation of the nidogen gene displays neurological abnormalities but does not result in aberrant epithelial morphogenesis (Dong et al, 2002). …”
Section: Search For the Critical Cell-ecm Adhesion Event(s) In Mdck Cmentioning
confidence: 99%
“…Nidogen is constitutively located in areas of epithelial-mesenchymal interactions where it is secreted by the resident fibroblasts (Fox et al, 1991;Marinkovich et al, 1993;Ekblom et al, 1994), which has been confirmed in experimental systems in vitro (Fleischmajer et al, 1995;Smola et al, 1998). In mammals two isoforms have been discovered, nidogen-1 which is the major form, and nidogen-2 (Kohfeldt et al, 1998), and knockout mice have been generated (Murshed et al, 2000;Dong et al, 2002;Schymeinsky et al, 2002) providing a more specific functional proof. The complete lack of either nidogen-1 or -2 did not produce an obvious phenotype in basement membrane structures or related functions.…”
Section: Introductionmentioning
confidence: 99%